Simulação e controle de um sistema de geração eólica para uma aplicação residencial - Mazzaro, Luis Guilherme Santos (Universidade Federal de São Carlos, 2025)
Wind energy has emerged as one of the leading renewable sources of electricity due to its low environmental impact and strong potential for deployment at both utility scale and in residential systems. This project aims to design and model a grid-connected wind generation system using MATLAB/Simulink. The proposed solution comprises the modeling of a small wind turbine, a permanent-magnet synchronous generator (PMSG), a three-phase rectifier, and a maximum power point tracking (MPPT) controller based on the Perturb and Observe method to optimize power extraction. The main challenges encountered were the integration of components in Simulink and the tool’s limitations in accurately representing the system, which required evaluating different control and energy-conversion strategies. The results confirm the feasibility of the modeled approach and highlight the potential of wind microgeneration as a sustainable alternative for residential applications, contributing to the diversification and decentralization of the energy mix.
Wind energy system control and simulation for residential application
Keywords: Energia Eólica; PMSG; Controlador MPPT; Modelagem; Matlab/Simulink; ENGENHARIAS::ENGENHARIA ELETRICA::SISTEMAS ELETRICOS DE POTENCIA::GERACAO DA ENERGIA ELETRICA; 7. Energia limpa e acessível